2007
DOI: 10.1002/app.26058
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanofibre‐reinforced ultrahigh molecular weight polyethylene for tribological applications

Abstract: Carbon nanofibre (CNF)-reinforced ultrahigh molecular weight polyethylene (UHMWPE) nanocomposites containing up to 10 wt % of nanofibres were prepared by a novel solvent-assisted extrusion process using short chain oligomers to tailor the melt viscosity of the UHMWPE matrix. A detailed investigation of the resulting nanocomposite microstructure and of the static mechanical properties revealed that the carbon nanofibres lead to improved mechanical properties of the UHMWPE related to the wear performance of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 38 publications
4
68
0
Order By: Relevance
“…In Xu's study, the addition of 0.5 wt% CNF resulted in an improved wear resistance, while a higher level CNF addition (3 wt%) resulted in a higher wear rate [64]. A similar trend was found in Galetz's study [62], in which with 5 wt% CNF, the nanocomposite showed a highly improved wear rate compared to the pure UHMWPE. Compared with 5 wt% CNF-reinforced UHMWPE, the wear rate increased at the presence of a larger CNF concentration (10 wt%).…”
Section: Fillers (Cnfs Cnts Graphene and Hard Particles)supporting
confidence: 63%
See 3 more Smart Citations
“…In Xu's study, the addition of 0.5 wt% CNF resulted in an improved wear resistance, while a higher level CNF addition (3 wt%) resulted in a higher wear rate [64]. A similar trend was found in Galetz's study [62], in which with 5 wt% CNF, the nanocomposite showed a highly improved wear rate compared to the pure UHMWPE. Compared with 5 wt% CNF-reinforced UHMWPE, the wear rate increased at the presence of a larger CNF concentration (10 wt%).…”
Section: Fillers (Cnfs Cnts Graphene and Hard Particles)supporting
confidence: 63%
“…Studies on the mechanical properties of CNF reinforced polyethylene revealed that the material's yield stress, tensile modulus and hardness increased by the addition of a certain amount of CNFs. For example, it was reported that incorporation of 5 wt% CNFs resulted in an approximately 25% increase in the tensile modulus, while increasing the CNF content to 10 wt% led to a slightly additional benefit [62]. Similar trends were also observed for the hardness of CNF reinforced UHMWPE material [62].…”
Section: Fillers (Cnfs Cnts Graphene and Hard Particles)mentioning
confidence: 56%
See 2 more Smart Citations
“…You & Li 24 reported that the incorporation of bamboo charcoal flour into the polyethylene improved the elastic recovery and decreased the recovered strain remarkably. Carbon-based fillers act as a solid lubricant reducing the coefficient of friction 25 , while also potentially improving other mechanical properties of the thermoplastic composites 26,27 .…”
Section: Mechanical Propertiesmentioning
confidence: 99%